DAMPAK KAWASAN INDUSTRI BATA MERAH TERHADAP KONDISI LAHAN DI DESA LEGU KECAMATAN SATAR MESE KABUPATEN MANGGARAI - Artoni, Edwardianus; Pamungkas, Bella Theo Tomi; Hasan, Muhammad Husain (Jurnal Geografi, 2024)
This research aims: 1) to determine the impact of the red brick industry on land conditions, 2) the population used in this reseerch was 30 people and the samples tsken were 15 people, consisting of 5 red brick industry owners, 6 workers, 3 people from the community near the red brick industrial area, and 1 village official, namely the head of Legu Village. This research is qualitative research and the method used in this research is descritive method. Data collection methods use interviews, observation and documentation methods. The development of the red brick industry in Legu Village has had an impact, both positive and negative, and for the positive in has increased income for the people who work and opened up employment opportunities for the community and the negative impact has been that the large amount of land used to meet the needs oh the red brick industry has caused damage, on lands, such as erosion of the surface of the land which results in reduced soil fertility, as well as the large amount of land being converted for the red brick industry which will result in a lot of damage to the land. The existence of the red brick industry in Legu Village provides income for workes and owners of the red brick industry which provides opportunities for those who need work to meet their daily living needs. The development of the red brick industry in Legu Village, which in this case can damage the land used, but can increase income for workes to meet their daily needs.